A classical-Keynesian model of macroeconomic fluctuations - Dibeh, Ghassan (1995)
The purpose of this paper is to construct a simple model of the capitalist economy that generates business cycles in an endogenous manner. Embedded relationships that permeate the interaction modes of economic agents are shown to be responsible for this characteristic macrodynamic phenomenon of market economies. These relationships are competing claims on income, the dual nature of the wage-profit relation, and the dependence of investment on profits. These relationships constitute institutional barriers within the market economy that prevent the attainment of full employment and equilibrium predicted by neoclassical theory. In the next section, a discussion of Marx's theory of the business cycle is presented. More attention is given to the reserve army of labor variant of Marx's cycle theory because it provides the link between labor market conditions and profits in the economy. Following that a theoretical review of the Keynesian vs. classical assumptions on the wage-profit relationship is presented. This paper argues, following recent macroeconomic models (Bowles and Boyer 1991; Marglin and Bhaduri 1991; Sherman 1991) that the capitalist economy generates an asymmetric macroeconomic regime structure. The macroeconomic regime, depending on employment or output levels, can be in either a cooperative Keynesian regime or a conflict-ridden Marxian regime. This paper Lebanese American University at Byblos, Lebanon. US address: 475 Riverside Dr.# 1846, New York, NY 10115. This paper is based on essay #3 of the author's dissertation titled "Essays in Buisness Cycle Theory" completed at the University of Texas at Austin in May 1994. The author wishes to thank Harry Cleaver, David Kendrick, Rafael de la Llave, Niles Hansen and Howard J. Sherman for their comments and encouragement. All errors remaining are mine. A Classical-Keynesian Model of Macroeconomic Fluctuations 13 further argues that this asymmetric structure is produced by the nonlinearity of the wage-profit relation. The paper develops a nonlinear business cycle model that takes into account this nonlinearity and the dependence of investment on profits. The model is shown to produce business cycle solutions endogenously.